Proceedings of the 18th International Seminar on Paste and Thickened Tailings 2015
DOI: 10.36487/acg_rep/1504_05_reid
|View full text |Cite
|
Sign up to set email alerts
|

The influence of slurry density on in situ density

Abstract: Since the beginning of the Paste and Thickened Tailings seminar series, there has been ongoing discussion as to whether an increase in the deposited (initial) slurry density will result in an increased density at depth within an accreting deposit, all else being equal. Despite frequent speculation and theorising, there has been relatively little laboratory data or other evidence presented at the conference series to address this question. To address the above deficiency, a literature review was undertaken to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“… Even for the same preparation method in the laboratory, pouring slurries of different (non-segregating) densities into consolidation test devices can also, in some cases, result in different non-converging NCLs. After a surprisingly long debate at various Paste and Thickened Tailings series seminars, this point was made clear by a literature review and further testing presented by Reid and Fourie (2015).…”
Section: Effects Of Deposition Conditions On Resulting Statementioning
confidence: 99%
“… Even for the same preparation method in the laboratory, pouring slurries of different (non-segregating) densities into consolidation test devices can also, in some cases, result in different non-converging NCLs. After a surprisingly long debate at various Paste and Thickened Tailings series seminars, this point was made clear by a literature review and further testing presented by Reid and Fourie (2015).…”
Section: Effects Of Deposition Conditions On Resulting Statementioning
confidence: 99%
“…This different range of achievable densities from different laboratory test methods has frequently been observed in low plasticity sandy materials (Ishihara 1993;Jefferies & Been 2000). Indeed, even different non-segregating slurry densities have been observed to result in different NCLs for some materials (Reid & Fourie 2015).…”
Section: Resultsmentioning
confidence: 79%
“…This indicated that the material was likely to be denser than the critical state in situ, and hence exhibit dilative behaviour. Recent interpretation (Reid & Fourie 2015) of in situ testing undertaken within the material suggests that the realised in situ states are somewhat denser than predicted from the laboratory testing, potentially resulting from air drying effects. Seddon (2007) obtained a residual strength ratio of 0.05 by means of vane shear testing within a portion of copper tailings undergoing air drying.…”
Section: Introductionmentioning
confidence: 90%